MINAT ORANGTUA MENYEKOLAHKAN ANAK DI LEMBAGA PAUD PADA MASA PANDEMI COVID-19 - Indah Maysela Azzahra; Ichsan Ichsan; Kiki Melita Andriani (Jurnal Anak Usia Dini Holistik Integratif (AUDHI), 2022)
Interest is a feeling such as being happy and interested in fighting for something or being happy and interested in doing something desirable. The purpose of this study was to find out parents who were interested in sending their children to school at PAUD institutions during the Covid-19 pandemic.  The research method used is the survey research method. The data collection technique used in this study was to use the questionnaire technique by distributing questionnaire instruments to respondents. The subjects of the study were parents who had children aged 4-6 years and sent their children to school in PAUD and kindergarten in Palembang city which became the criteria for selecting samples. So, the sampling technique uses purposive sampling techniques. The data analysis technique used is quantitative descriptive statistics with percentages, percentage results will then be described based on the category of parents' interest in sending their children to PAUD institutions. The results of the study obtained the most respondents who were interested in sending their children to PAUD institutions as many as 38% of respondents and categorized into moderate interests. The average respondent/parent who has an interest in sending their children to school in PAUD institutions is influenced by factors of parents' personal needs and goals/motives, school factors, and community factors are relatively high. However, family factors and the Covid-19 Pandemic also caused respondents not interested in sending their children to ecclesiastical institutions to be the same high. Based on the data obtained, the conclusion is that there is a lack of interest in parents sending their children to early childhood institutions during the Covid-19 pandemic